Chiastic Structure of the Vessantara Jataka: Textual Criticism and Interpretation Through Inverted Parallelism - Huifeng, Shi (Buddhist Studies Review, 2015)
The Vessantara Jataka is not only the most popular of all the Buddhist Jataka tales, but is important in the tradition as a whole, generally considered by the Theravadin tradition to display the epitome of the Bodhisatta’s perfection of giving (danaparami). While most studies have focused on philological approaches, numerous questions as to the text’s structure and how to interpret individual parts within that structure have remained unresolved (§1. The received tradition of the Vessantara Jataka). My study shall employ the theory of ‘chiasmus’ (inverted parallelism) to shed new light on both the key message of the story and also the sub-themes within it (§2. Chiastic structures as textual approach). In terms of textual criticism, I shall first elucidate the chiastic structure of the text and discuss how this structure can provide insights on text-critical readings (§3. Textual criticism: Chiastic units and structure). In terms of interpretation, I shall then see how the structure clearly demarcates the text’s scope through its prologue and conclusion with surrounding framework, its paired parallel sub-themes, and its central climax point, all in the light of its chiastic structure (§4. Interpretation: A chiastic reading). Finally, considering broader implications, on comparison with other recently discovered Buddhist textual chiasmi I shall present a tentative hypothesis as to the origins of such structures in the ‘bodhisatt(v)a’ literary genre (§5. Conclusions: Critical and interpretive implications).